The Influence of Brand Image and Brand Reputation on Purchase Decision at Lazada: A Study of the Community in Pontianak City - Rindi Artika; Ananda Archie (Electronic Journal of Education, Social Economics and Technology, 2025)
The rapid development of the e-commerce industry in Indonesia, particularly Lazada, has changed consumer shopping patterns. In the world of e-commerce, brand image and brand reputation are key factors influencing consumer purchase decision. Increasing competition among e-commerce platforms requires companies to strengthen their brand image and reputation in order to attract consumers and increase loyalty. This study aims to analyze the influence of brand image and brand reputation on purchase decision on the Lazada platform in Pontianak City. This study uses a quantitative approach with an association method, where data was collected through the distribution of questionnaires to 100 respondents who had made purchases on Lazada. The analysis techniques used are multiple linear regression, validity and reliability tests, as well as classical assumption tests such as normality, linearity, and multicollinearity tests. The results of the F-test in this study indicate that brand image and brand reputation simultaneously have a significant influence on purchase decision on Lazada. The results of the t-test show that brand image and brand reputation have a positive and significant partial influence on purchase decision. This highlights the importance for companies to pay attention to and improve their brand image and reputation in creating a positive shopping experience for consumers. This study provides new insights into how brand image and brand reputation simultaneously influence purchase decision in the context of e-commerce in Indonesia, particularly on the Lazada platform, and can serve as a foundation for companies to formulate more effective marketing strategies in facing increasingly intense competition.